Art, Imagination and (Technical) Creativity in the Philosophy of Emilio Garroni - Cecchi, Dario (Aesthetica Preprint, 2023)
The theory of creativity Emilio Garroni develops in the late 1970s and recovers in the early 2000s inside his original philosophy of the imagination demolishes some of the commonplaces concerning this concept. On the one hand, the human creativity is rooted in the context of an operativity that concerns all the fields of the human action; on the other hand, it is considered a previously unforeseeable capability of designing, discovering and experimenting. From this point of view, art has no superiority in the field of creativity: reconsidering the relationships between art and technics may be rather useful. Garroni eventually thinks of art as a non-finalized exercise of creativity, bound to knowledge and technical operativity, through which homo sapiens is able to critically reflect upon the anxiety engendered by the very technical progress started with their creative power. Art can be therefore reconsidered, in the age of the Anthropocene, as a tool for promoting critical thinking.